Unified Banks draft law on the Central Bank, the banking machinery, and the foreign exchange / Translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Unified banks draft law on the central bank the banking machinery the foreign exchange – part 1 – part 2 – part 3 – part 4 – part 5 – part 6 – part 7